2007
DOI: 10.1016/j.brainres.2007.09.087
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of pair-bonding in a monogamous primate

Abstract: The neurobiology of social bonding, despite its relevance to human mental health, has been studied primarily in rodents. In this study we used position emission tomography (PET), registered with structural magnetic resonance imaging (MRI) to investigate central glucose uptake in seventeen males of a monogamous primate species, the titi monkey (Callicebus cupreus). Twelve pair-bonded males (including six with a lesion of the prefrontal cortex) and five lone males were scanned. The five lone males were re-scanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 55 publications
4
92
0
Order By: Relevance
“…AVP receptor distributions in monogamous marmosets (91,92) and titi monkeys (93), as well as in polygnous rhesus macaques (94), parallel those observed in monogamous and promiscuous voles, respectively, confirming that this reward pathway functions similarly in primates. Although receptor distributions such as those now available for some monkey species are not yet available for humans, there are marked parallels in other related cerebral phenomena revealed by functional magnetic resonance imaging (see also below).…”
Section: Owen Lovejoysupporting
confidence: 60%
“…AVP receptor distributions in monogamous marmosets (91,92) and titi monkeys (93), as well as in polygnous rhesus macaques (94), parallel those observed in monogamous and promiscuous voles, respectively, confirming that this reward pathway functions similarly in primates. Although receptor distributions such as those now available for some monkey species are not yet available for humans, there are marked parallels in other related cerebral phenomena revealed by functional magnetic resonance imaging (see also below).…”
Section: Owen Lovejoysupporting
confidence: 60%
“…These data have contributed to the hypothesis that pair bonds represent social addictions between mating partners, mediated in part by organization and plasticity of mesolimbic DA pathways [33]. Studies in the zebra finch and coppery titi monkey have also reported reorganization in mesolimbic reward areas following bond formation, suggesting that neural plasticity in these pathways may be an evolutionarily conserved feature of pair bonding across species [34,35]. …”
Section: Mesolimbic Dopamine System In Pair Bond Formationmentioning
confidence: 99%
“…Functioning in these ways, OT plays an important role 82 in positive social interactions, such as grooming, sex, childbirth 83 and parental care (Carter et al, 2008). OT has also been associated 84 with social signaling (Bales et al, 2007a;Bales et al, 2007b;Bales 85 et al, 2007c), and deficits in the processing of social information 86 have been linked to low OT levels (Takayanagi et al, 2005). 87 Furthermore, it has been suggested that the social deficits in 88 certain autism spectrum disorders in humans might be related to 89 low levels of OT (Wu et al, 2005;Jacob et al, 2007;Gregory 90 et al, 2009), although inconsistent findings relating oxytocin to 91 autism have been noted (Tansey et al, 2010).…”
mentioning
confidence: 96%